1994
DOI: 10.1111/j.1365-2915.1994.tb00095.x
|View full text |Cite
|
Sign up to set email alerts
|

Vectors of cutaneous leishmaniasis in north‐central Venezuela

Abstract: An entomological survey was undertaken from January 1991 to February 1992 in El Ingenio, Miranda State, Venezuela, an endemic area of cutaneous leishmaniasis: prevalence of 10.7 cases per 100,000 inhabitants. A total of 4863 female sandflies (Phlebotominae) of fourteen species were collected in Shannon traps, then dissected and examined for leishmanial infections. Lutzomyia ovallesi (85.4%) and Lu. gomezi (11.2%) were the predominant anthropophilic species of sandfly. Fifty-one (1.19%) Lu.ovallesi and two (0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
12

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 23 publications
1
35
0
12
Order By: Relevance
“…Fax: ++58 243 242 5333 -E-mail: mdora@telcel.net.ve (DL) (from Files of the Departmento de Informática, Instituto de Biomedicina, Caracas). About 100 species of phlebotomine sandflies are known in Venezuela, 30 of which are anthropophilic and eight are recognized as suspected or proven vectors of CL (Feliciangeli, 1991). In Southern Venezuela, the Amazonian region, no studies on the natural infection in phlebotomine sandflies have been carried out and Lutzomyia umbratilis Ward & Fraiha 1978, Lutzomyia anduzei (Rozeboom, 1942, Lutzomyia flaviscutellata (Mangabeira, 1942) and species in the subgenus Psychodopygus are suspected to be responsible for the transmission of CL on the basis of their anthropophily and because elsewhere they are recognized as proven vectors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fax: ++58 243 242 5333 -E-mail: mdora@telcel.net.ve (DL) (from Files of the Departmento de Informática, Instituto de Biomedicina, Caracas). About 100 species of phlebotomine sandflies are known in Venezuela, 30 of which are anthropophilic and eight are recognized as suspected or proven vectors of CL (Feliciangeli, 1991). In Southern Venezuela, the Amazonian region, no studies on the natural infection in phlebotomine sandflies have been carried out and Lutzomyia umbratilis Ward & Fraiha 1978, Lutzomyia anduzei (Rozeboom, 1942, Lutzomyia flaviscutellata (Mangabeira, 1942) and species in the subgenus Psychodopygus are suspected to be responsible for the transmission of CL on the basis of their anthropophily and because elsewhere they are recognized as proven vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Lutzomyia ovallesi is the most widespread vector of CL below 800 m a.s.l. in Venezuela, and has been found infected in several foci: El Ingenio, Miranda State (north-central Venezuela) with Leishmania (Viannia) braziliensis and Leishmania (Leishmania) mexicana (Feliciangeli, 1991;Feliciangeli et al, 1994;Barrios et al, 1994); in Duaca, Lara State (west-central Venezuela) it was found harboring a hybrid Le. braziliensis-Le.…”
Section: Introductionmentioning
confidence: 99%
“…Actualmente, la detección de parásitos del género Leishmania en los insectos incluye métodos que van desde la búsqueda directa de los flagelados en el tracto digestivo del insecto hasta técnicas moleculares que usan principalmente K ADN (12,(26)(27)(28)(29)(30). La técnica de reacción en cadena de la polimerasa (PCR), por su alta sensibilidad y especificidad, ha facilitado adelantar estudios ecoepidemiológicos en áreas de alta endemicidad, suministrando datos más precisos en periodos de tiempo más cortos (17,29).…”
Section: Discussionunclassified
“…De las once especies de Lutzomyia capturadas, se destacan por su De manera accidental se capturó un ejemplar carácter antropofílico y sus antecedentes como dentro de una vivienda del barrio Chorreras de vectores, L. ovallesi, L. gomezi, L. quasitown-Don Juan, aledaña al bosque Chorreras, picando sendi, L. lichyi y L. shannoni sobre humano, lo que refleja sus hábitos endofilicos v antro~ofílicos como se ha descrito L.ovallesi es vector confirmado de L. en otros estudios. Por su amplia distribución, braziliensisen Guatemala y Venezuela (18,19). sus antecedentes como vector y sus hábitos En Bélice, Colombia y Panamá se ha encontra-antropofílicos, esta especie podría estar implicado con flagelados no identificados (2,20,21).…”
Section: Discussionunclassified
“…gomezi es una especie altamente antropofílica, aunque pica a una gran variedad de mamíferos; ha sido encontrada naturalmente infectada por L. braziliensis en Venezuela (19). En Colombia, esta especie tiene una distribución muy amplia y es frecuente en focos de leishmaniasis cutánea y visceral (22, 23), además, en barrios periféricos de algunas ciudades (15).…”
Section: Discussionunclassified